Effects of chicken manure substitution for mineral nitrogen fertilizer on crop yield and soil fertility in a reduced nitrogen input regime of North-Central China - Ning, Linyirui; Xu, Xinpeng; Zhang, Yitao; Zhao, Shicheng; Qiu, Shaojun; Ding, Wencheng; Zou, Guoyuan; He, Ping (Frontiers in Plant Science, 2022)
Organic manure has been proposed to substitute part of the chemical fertilizers. However, past research was usually conducted in regimes with excessive nitrogen (N) fertilization, which was not conducive to the current national goal of green and sustainable development. Therefore, exploring the potential of organic fertilizer substitution for mineral N fertilizer under regimes with reduced N inputs is important to further utilize organic fertilizer resources and establish sustainable nutrient management recommendations in the winter wheat (Triticum aestivum L.) – summer maize (Zea mays L.) rotation system in North-central China. In this study, a 4-year field experiment was conducted to investigate the effects of different chicken manure substitution ratios on crop yield, N recovery efficiency (REN), soil N and soil organic matter contents, to clarify the optimal organic substitution ratio of N fertilizer under reduced N application (from 540 kg N ha−1 year−1 to 400 kg N ha−1 year−1). Six substitution ratios were assessed: 0%, 20%, 40%, 60%, 80% and 100% under 200 kg N ha−1 per crop season, respectively, plus a control with no N application from chemical fertilizer or chicken manure. Results showed that the highest yield was achieved under the 20% substitution ratio treatment, with 1.1% and 2.3% higher yield than chemical N alone in wheat season and maize seasons, respectively. At the chicken manure substitution ratios of 20% in wheat season and 20%-40% in maize season, the highest REN reached to 31.2% and 26.1%, respectively. Chicken manure application reduced soil residual inorganic N with increasing substitution ratio. All organic substitution treatments increased soil organic matter and total N content. Implementing 20% organic substitution in wheat season and 20%-40% in maize season under the reduced N application regime in the North-central China is therefore recommended in order to achieve high crop yields and REN, improve soil fertility and enhance livestock manure resource utilization.